Determinan Minat Berinvestasi Mahasiswa di Pasar Modal - Ni Putu Sriasih; Made Arie Wahyuni (Ekuitas: Jurnal Pendidikan Ekonomi, 2020)
The purpose of this study was to determine the effect of investment knowledge, minimum investment capital and technological advances on investment interest in the capital market. This study uses a quantitative approach. Data were collected using a questionnaire as a research instrument. The data used is primary data because data is obtained directly from respondents' answers to the statements contained in the questionnaire. The population in this study were all students of the S1 Accounting Study Program, Faculty of Economics, Ganesha University of Education. The sampling technique used purposive sampling method, so that 245 respondents were obtained. This study uses multiple linear regression analysis techniques assisted by the SPSS 20.0 for Windows program. The results of this study indicate that investment knowledge (X1), minimum investment capital (X2) and technological progress (X3) each have a positive effect on the interest in investing in the capital market.